Curriculum Development and The Concept of Social Science Education in Indonesia - Rahmi Hidayat (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
This article aims to describe the development of Social Studies in Indonesia, both in the form of the concept of Social Studies education and adaptation to the development of the Social Studies curriculum in Indonesia. Social Studies (IPS) is not an independent science. In Social Sciences, much material from various social sciences is used or adapted to get what you want to achieve in the chosen education or teaching. Social Studies is an integrated study material, namely selection, adaptation, and regulated (organized) modification of scientific concepts, such as historical, economics, geography, sociology, and anthropology skills). Social Studies is a subject designed to improve/develop knowledge, skills, and understanding in analyzing social conditions in society, especially when entering the life of a dynamic society. In Indonesia, Social Studies is described in an integrated, dynamic, and comprehensive way for the flow of learning activities in order to achieve success and maturity in societal attitudes. Indonesia has a dynamic educational development and participates in the times. This is interesting to study in more detail through historical studies on developments in Indonesia for social studies education, starting from the first entry of social studies education to developments in schools related to the curriculum. Indonesia has a dynamic educational development and participates in the times. This is interesting to study in more detail through historical studies on developments in Indonesia for social studies education, starting from the first entry of social studies education to developments in schools related to the curriculum. Indonesia has a dynamic educational development and participates in the times. This is interesting to study in more detail through historical studies on developments in Indonesia for social studies education, starting from the first entry of social studies education to developments in schools related to the curriculum.